The relationship and time elasticity between traffic location change and urbanization process: a case study of China's Chongqing municipality. Issue 2 (3rd July 2018) - Wang, Yang; Wang, Li-li; Qi, Peng-wei; Liu, Zhi-hai
ABSTRACT: The improvement of traffic location conditions is an important driving force for the development of regional urbanization. Establishing a quantitative correlation model between them is the basic premise for finding out the evolution rules of regional development patterns. Taking China's Chongqing Municipality as an example, through Regional Traffic Dominance (RTD) modelling, this paper quantitatively analyzed the time-series response relationship between the evolution of RTD and urbanization in the past 10 years. The results show that there is a strong positive correlation between RTD and urbanization. Meanwhile, the temporal-elasticity is following a certain pattern determined by the grade of transport network.